Relationship Between Mothers' Parenting Styles, Muslim Adolescents' Personality, Self-Esteem and Academic Achievement - Mansor, Norwati (2010)
Previous research studies of parenting styles and self-esteem have been explored extensively in the context of the Western perspective. In Islamic perspective, mothers are considered as the first educators for their children. Thus, there is a need to investigate the impact of mothers’ parenting styles and Muslim adolescents’ personality in the Muslim orientation. Previous research studies of student academic achievement has been linked to self-esteem but nevertheless did not relate to parenting styles and personality among adolescent Muslims. Thus, this present study was designed to fill in the literature gaps that exist in this area. This study employed ex-post facto design. Generally, the purpose of this study was to propose a model of mothers’ parenting styles and adolescents’ factors. Specifically the model was estimated to measure the relationships between mothers’ parenting styles (authoritarian, authoritative and permissive), Muslim adolescents’ personality, self-esteem and academic achievement. The instruments adaptation in this study was designed quantitatively and distributed to a sample size of 360 students’ ages 15 years old (Form Three) from Islamic religious schools under the Selangor State Islamic Religious Department. The selections of schools were based on multistage cluster sampling. Using Structural Equation Modeling analysis, the study has to re-specify the hypothesized model due to any insignificance of relationships between authoritarian and permissive mothers’ parenting styles towards Muslim adolescents’ personality. The findings have revealed that authoritative mothers’ parenting style influenced the Muslim adolescents’ personality significantly. In addition, Muslim adolescents’ personality gave an impact to self-esteem. As a result, self-esteem will promote academic achievement among the Muslim adolescent students in the selected Islamic religious schools. The results have given implications to parents, counselors, teachers and policy makers. In addition, these findings will hopefully help to contribute to an extension of the literature reviews and methodology.